Sensitivity of a renal K+ channel (ROMK2) to the inhibitory sulfonylurea compound glibenclamide is enhanced by coexpression with the ATP-binding cassette transporter cystic fibrosis transmembrane regulator. - McNicholas, C M (1996)
We demonstrate here that coexpression of ROMK2, an inwardly rectifying ATP-sensitive renal K+ channel (IKATP) with cystic fibrosis transmembrane regulator (CFTR) significantly enhances the sensitivity of ROMK2 to the sulfonylurea compound glibenclamide. When expressed alone, ROMK2 is relatively insensitive to glibenclamide. The interaction between ROMK2, CFTR, and glibenclamide is modulated by altering the phosphorylation state of either ROMK2, CFTR, or an associated protein, as exogenous MgATP and the catalytic subunit of protein kinase A significantly attenuate the inhibitory effect of glibenclamide on ROMK2. Thus CFTR, which has been demonstrated to interact with both Na+ and Cl- channels in airway epithelium, modulates the function of renal ROMK2 K+ channels.